Environmental and biological study of the effluents of the Danafi Valley and its impact on the water quality of the Tigris River in the city of Mosul, Iraq - Abdulazeez Al-Safawi; Azhar Al-Assaf (College of Education for Pure Sciences, 2014)
The present study includes ecological properties of danfeeli valley which is located at the south eastern part of Mosul city of Iraq. Danfeeli valley transports seasonal rainfall water domestic and industrial wastes to Tigris river, so that, creates additional water pollution of this river, water samples were collected from five stations along the valley inside Mosul city to examine the physical, chemical, and biological properties, as well as, the role of self purification in elimination of the pollution problems, Also, samples of Tigris river were collected to determine the effect of polluted valley water on the river water parameters. Results of the present study indicates for dimension of dissolved oxygen in the valley water especially dty Dryweather due to high biological oxygen demand which reachs to 177.4 mg/L in one of some warm month. Relative increase in sulphate ions concentration was found as a result of proteolysis of protein matters in the valley water. The dominant phytoplankton genera were: Clamydomonas. Euglena, Fragelaria, Nitizschia and Navicula. It was found high significant pollution effect of Danfeeli wastewater on Tigris river at station 50 m south meetings, this deterioration was continued till at station 250 m, therefore, ecosystem pollution will be increased later. Also it was investigated the relative effect of self purification event (pathways) on some investigated parameters of water wastes through its streaming in the valley; namely, biological oxygen demand, chloride ions, sulphate ions and phosphate ions. It was considered that Danfeeli and Tigris water proper for irrigation usages for pH, sodium percentages sodium adsorption ratio, residual sodium carbonate and potential salinity. However, some problems in salinity were obtained according to standard international classifications.